'Meiotic genes' are constitutively expressed in an asexual amoeba and are not necessarily involved in sexual reproduction. (29th March 2019) - Maciver, Sutherland K.; Koutsogiannis, Zisis; de Obeso Fernández del Valle, Alvaro
Abstract : The amoebae (and many other protists) have traditionally been considered as asexual organisms, but suspicion has been growing that these organisms are cryptically sexual or are at least related to sexual lineages. This contention is mainly based on genome studies in which the presence of 'meiotic genes' has been discovered. Using RNA-seq (next-generation shotgun sequencing, identifying and quantifying the RNA species in a sample), we have found that the entire repertoire of meiotic genes is expressed in exponentially growing Acanthamoeba and we argue that these so-called meiotic genes are involved in the related process of homologous recombination in this amoeba. We contend that they are only involved in meiosis in other organisms that indulge in sexual reproduction and that homologous recombination is important in asexual protists as a guard against the accumulation of mutations. We also suggest that asexual reproduction is the ancestral state.